HUBUNGAN KESEHATAN DAN KESELAMATAN KERJA DENGAN KINERJA KARYAWAN STUDI KASUS PABRIK GULA X, SIDOARJO - Randie Andriawan (Jurnal Informasi, Perkebunan dan Sipil, 2022)
Objective of this research is to know what is the correlation between safety work policy and employee performance in X Sugar Factory, Sidoarjo. X Sugar Factory is the company that produce sugar and processing cane. In the operation this company of course had a factory that used to processing cane to produce sugar. Thats why we need to know and analyze the implemented policy about safety work in this company, that is so important for safety work environtmen for the employee. This research collected primary and secondary data. Primary data collected by researcher and secondary data is about incident and safety work implementation in X Sugar Company. The research result showed that there is a positive and real correlation between safety work policy and employee performance. From that we know improvement in safety work policy is usefull to increase the employee performance in X Sugar Factory.